DIVUSI INOVASI PENILAIAN PEMBELAJARAN HIGHER ORDER THINKING SKILL (HOTS) PADA SEKOLAH DASAR - Rizal; Surahman; Moh Aqil; Azizah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The standard of assessment for elementary schools in Donggala Regency is only at level 2 reaching 2.59% (low category). This happens, because the application of higher-order thinking skills in elementary schools in Donggala District, especially Banawa District, is not optimal. So the research was conducted to reveal data on the ability of teachers in carrying out HOTS-oriented learning assessments. This study uses a quantitative and qualitative approach. This research was carried out by the Elementary School in Banawa District, Donggala Regency by determining the sample using purposive sampling. Data was collected by means of questionnaires and interviews. Data analysis techniques are data collection, data reduction, data presentation, and verification. The results showed that of the 30 elementary schools in Banawa District, only 13 schools or 45% had known and obtained information about HOTS-oriented learning assessment. It was concluded that (1) the assessment of HOTS-oriented learning in elementary schools throughout Banawa sub-district was not yet understood (2) the government and stake holders as well as the school had not utilized the existing information channels to convey and exchange information about HOTS, (3) sufficient time was needed to distribute information about HOTS. HOTS in order to form a diffusion of innovation (4) in this case the social system or teacher group work (KKG) has not become a forum for distributing information about HOTS assessment in elementary schools throughout Banawa District, Donggala Regency.